Comparation of Corn Cob Charcoal and Lamtoro (Leucaena leucocephala) Wood as an Adsorbent for Used Cooking Oil - Hanun Busro; Aisyah Qurrota Aini; Aulia Zahra Isnaini; Na’ilah Hanin Rahadatul A’isyi; Maylan Ulayya Firstyaska Asyari (SMA Trensains Muhammadiyah Sragen, 2023)
The background of this research is the lack of utilization of corncob waste and lamtoro wood. The purpose of this study was to determine the adsorption ability of corn cob activated charcoal and Leucena leucocephala wood to used cooking oil in reducing free fatty acid levels. The research method used in this research is experimental. This study consisted of four stages, namely the manufacture of activated charcoal, purification of used cooking oil, determination of free fatty acid levels, and calculation of viscosity values. 1.2%, decreased viscosity value from 1.68 Ns/m² to 1.63 Ns/m², and color change from blackish brown to slightly brownish yellow. Meanwhile, purification of used cooking oil using activated charcoal Leucena leucocephala decreased FFA levels from 1, 58% to 1.4%, a decrease in the viscosity value from 1.68 Ns/m² to 1.3 Ns/m², and a color change from blackish brown to brownish yellow. This shows that the purification of used cooking oil using activated charcoal from corn cobs is considered more effective than using activated charcoal from lamtoro wood. This is because the FFA levels of used cooking oil purification using corncob activated charcoal are of lower value, clearer color after purification, and higher viscosity value.